Multi-Criteria Decision-Making Method with Fermatean Fuzzy Soft Sets and Application of Infectious Diseases - Demir, Ibrahim (Fuzzy information and engineering, 2024)
Fermatean fuzzy soft set is the most powerful and effective extension of Fermatean fuzzy sets which deals with the parametrized values of the alternatives. It is also a generalization that provides better and more precise information in the decision-making process compared to Pythagorean and intuitionistic fuzzy soft sets. In this study, “OR” and “AND” operations and some different algebraic operations will be given. Then, some basic properties have been established for the Fermatean fuzzy soft set employing the improved operations. Furthermore, a decision-making approach has been suggested for the Fermatean fuzzy soft set based on a score matrix. To demonstrate the validity of the proposed approach, a numerical example has been presented.